Climate Change for Bilingual Students in Indonesian Language Learning with Translanguaging Learning Model - Fathiaty Murtadho; Endry Boeriswati; Rosa Amelia Cristina Pardede (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The learning model, especially in learning Indonesian for bilingual students, is certainly different from non-bilingual students. The ideology used in Indonesian learning would obviously affect the learning climate in the classroom. In learning Indonesian, educators use an ideology that requires students to use the language itself. This research aims to develop an Indonesian learning design with a translanguaging approach. This approach will accommodate all bilingual students' linguistic repertoire ability in learning Indonesian as a second language and this model is expected to change the Indonesian learning climate for bilingual students. The method used in this study is Research and Development (R&D) with three stages, namely 1) Needs analysis. 2) Product draft development. 3) Expert validation and product user trials. The results of the needs analysis found from the student and teacher questionnaires showed that bilingual students had difficulty in learning Indonesian. The development of the draft was carried out based on the theory of the translanguaging approach that had been carried out in previous research in foreign languages. The components of the model developed include learning stages, social systems, reaction principles, support systems, and instructional and accompanying impacts. The results of the validation test, the development of this model is feasible to use and from the results of the trial in the field, there is a change in the learning climate in the classroom using this translanguaging learning model.